Reclaiming multilateralism : for people, rights and sustainable - Adams, Barbara (UN New YorkUS, 2012)
Looks at the past and present of multilateralism. Analyses some of the underlying reasons why multilateral governance has not lived up to human rights and sustainable development objectives, notably in relation to contemporaneous issues of power and participation, flawed development models and major fault-lines plaguing the multilateral system today.